Philanthropic Fund Raising for Higher Education - Haseeb, A.S.M.A. (Journal of Research Management and Governance, 2018)
With the recent trend towards mass higher education, funding for higher education has become an important issue around the globe. Many governments do not seem to be able to afford it. Economic crisis from time to time makes the situation even worse. Fundraising by universities from alternative sources is increasingly being discussed. This article intends to give an introduction to philanthropic fundraising for higher education and research. Early history of fundraising for higher education and fundraising scenarios in the US, UK and EU are presented. Different models of university fundraising is outlined. Some thoughts on the potential of university fundraising in the Malaysian context are presented towards the end.